Manfaat Perilaku Spiritual Sufi Pada Kesehatan Mental dan Well Being Seseorang - Saliyo, Saliyo (Faculty of Ushuluddin and Humanities, 2018)
The purpose of this article is to know the connection of Sufi spiritual behavior with mental health in the form of well-being performed by the spiritual Sufi path. This article explores Sufi spiritual behavior with regard to mental health in the form of well-being that comes from literature.The method used in this research is qualitative research in the literature review. How to collect research data by researchers by writing, classifying and monitoring subjects of research studies carried out by researchers. Moreover, researchers conducting a survey of data collected related to the subject matter of the research is a spiritual relationship to mental health.The results of the literary research show that mystical spiritual behavior towards mental health, especially in the field of well-being, remains controversial. Sufi spiritual behavior has a positive effect. On the other hand, there are also results that mystic behavior has a negative effect. This incident occurred because of misunderstanding or perception of Sufi teachings, or lack of good guidance for the person in taking the Sufi path.